Augmented DNA Nanoarchitectures: A Structural Library of 3D Self‐Assembling Tensegrity Triangle Variants (Adv. Mater. 49/2022). Issue 49 (8th December 2022) - Woloszyn, Karol; Vecchioni, Simon; Ohayon, Yoel P.; Lu, Brandon; Ma, Yinglun; Huang, Qiuyan; Zhu, Eric; Chernovolenko, Daniel; Markus, Tiffany; Jonoska, Nataša; Mao, Chengde; Seeman, Nadrian C.; et al.
Abstract : Tensegrity Architectures In article number 2206876, Ruojie Sha and co‐workers develop a structural library of augmented tensegrity architectures based on geometric expansion of triangular tiles. The highly asymmetric structure highlighted in the crystal lattice contains three linearly independent design axes that lay the foundation for the self‐assembly of designer, heterogenous nanomaterials.